E-commerce adoption and farmers’ pesticide reduction behavior: implications for food system security - Qiu, Hailan; Tang, Wenyi; Deng, Hanyun; Hu, Lun; Wang, Jiawei; Sheng, Biao; Liao, Wenmei (Frontiers in Nutrition, 2025)
IntroductionReducing pesticide is an important measure to ensure the quality and safety of agricultural products and promote the development of organic agriculture. E-commerce effectively promotes the reduction of pesticide use by guiding consumers’ demand for agricultural products with low pesticide residues.MethodsTaking 3531 farmers in China as a sample, this paper analyzes the impact and mechanism of e-commerce adoption (ECA) on farmers’ pesticide reduction behavior (FPRB) by using the binary Logit model and mediation effect model, and investigates the heterogeneous impact of ECA on FPRB. On this basis, the differences in the effects of different e-commerce scales, modes and pesticide application methods are further discussed.Results and discussionThe research findings demonstrate that ECA effectively promote FPRB, with agricultural income expectations, food safety perception, and adoption of agricultural machinery socialization services serving as positive mediating factors. Heterogeneity analysis reveals that the impact of ECA on FPRB varies across individual levels, family levels, and regional levels. Further exploration indicates that large-scale e-commerce platforms and socialized e-commerce models exhibit more significant effects in FPRB, while ECA better facilitate farmers’ adoption of mechanized pesticide application methods. By quantifying the impact of ECA on FPRB, this study demonstrates the effective role of e-commerce in expanding the three core benefits of ecological protection, product safety and sustainable development of organic agriculture, and provides important reference and empirical enlightenment for the development of e-commerce and the green transformation of agriculture in developing countries.